The effect of adding neuromuscular electrical stimulation to exercise therapy on patellofemoral pain: A systematic review and meta-analysis. - Jiawei Zheng; Zixuan Wei; Huiwu Zuo; Kunpeng Wang; Xikai Lin; Jian Chen (PLoS ONE)
Background This study investigated the effects of adding neuromuscular electrical stimulation (NMES) to exercise therapy on pain, knee function, quadriceps strength, and the ratio of activation of the Vastus Medialis Oblique (VMO) to Vastus Lateralis (VL) muscles in people with Patellofemoral pain (PFP). Methods A rigorous search for randomized controlled trials (RCTs) spanning database inception to July 1, 2024, was executed across PubMed, Embase, Web of Science, Cochrane Library, and Scopus. Two researchers independently screened the literature and extracted data. The Cochrane Risk of Bias Tool was used for included studies to assess risk of bias and the GRADE system was used to assess the certainty of evidence for outcomes. Result Nine randomized controlled trials, encompassing 337 participants (171 intervention, 166 control), were included in the analysis. The meta-analysis findings indicated that compared to exercise therapy alone, NMES combined with exercise therapy significantly reduces pain intensity (MD: -0.37; 95% CI: -0.64 to -0.10; P = 0.007), notable improvements in knee function (MD: 4.76; 95% CI: 2.08 to 6.84; P = 0.0002), and significantly increased quadriceps muscle strength (SMD: 0.55; 95% CI: 0.24 to 0.87; P = 0.0006). However, there was no significant impact observed on the VMO/VL ratio (SMD: 0.8; 95% CI: -0.33 to 1.93; P = 0.16). Subgroup analyses superimposed that incorporating NMES did not result in a meaningful reduction in pain intensity (MD: -0.85; 95% CI: -1.76 to 0.07; P = 0.07) or a significant improvement in quadriceps muscle strength (SMD: 0.27; 95% CI: -0.24 to 0.78; P = 0.30) when the treatment period was less than or equal to 4 weeks. Conclusion The study's findings revealed that adding NMES to exercise therapy offers further improvement in pain intensity, knee function, and quadriceps strength in people with PFP compared with exercise therapy alone, but did not significantly improve VMO/VL ratio, and it recommended that the duration of the intervention lasts more than4 weeks for better therapeutic outcomes.